Progress of Travancore under H.H. Sree Moolam Tirunal - Paramēśvarayyar, Uḷḷūr Es (Dept. of Cultural Publications, Govt. of Kerala, 1998)
Progress of Travancore princely state under Maharaj of Travancore Sree Moolam Tirunal, 1857-1924.